Cars 2 (Parrogon Books Ltd, 2014)
Lightning McQueen enters the World Grand Prix in the hope of being crowned the world's fastest race car. Meanwhile his best friend, Mater, has become caught up in a spy adventure!...
Keywords: Juvenile Fiction / Adventure